2003
DOI: 10.1016/s0550-3213(03)00232-3
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear supersymmetry in quantum mechanics: algebraic properties and differential representation

Abstract: We study the Nonlinear (Polynomial, N -fold,...) Supersymmetry algebra in one-dimensional QM. Its structure is determined by the type of conjugation operation (Hermitian conjugation or transposition) and described with the help of the Super-Hamiltonian projection on the zero-mode subspace of a supercharge. We show that the SUSY algebra with transposition symmetry is always polynomial in the Super-Hamiltonian if supercharges represent differential operators of finite order. The appearance of the extended SUSY w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
201
0
3

Year Published

2005
2005
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(206 citation statements)
references
References 68 publications
2
201
0
3
Order By: Relevance
“…The extension cannot be, however, the standard N-extended one because the number of the degeneracy between "bosonic" and "fermionic" degrees of freedom is necessarily even. We have discussed two possible extensions [53,54,55,56,57,58,59] [60]. An interesting fact is that both of them are nonlinear extensions of the N = 2 supersymmetry algebra.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extension cannot be, however, the standard N-extended one because the number of the degeneracy between "bosonic" and "fermionic" degrees of freedom is necessarily even. We have discussed two possible extensions [53,54,55,56,57,58,59] [60]. An interesting fact is that both of them are nonlinear extensions of the N = 2 supersymmetry algebra.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…(III.45) is given by the square of the Hamiltonian H but not the linear of it. The system with the nonlinear algebra has been discussed in [53,54,55,56,57,58,59] as an extension of the N = 2 supersymmetry. Another type of extensions of the N = 2 supersymmetry has also been discussed in [60].…”
Section: Supersymmetrymentioning
confidence: 99%
“…[1,2], where it was also shown that Π N is proportional to the characteristic polynomial of the restriction of the component Hamiltonians…”
Section: N -Fold Superalgebra and Associated Polynomial Familiesmentioning
confidence: 96%
“…Indeed, in the proof of the theorem on SUSY algebras with T symmetry in Ref. [36], we only need to modify the functions w ± N in Eq. (6) in Eq.…”
Section: N -Fold Supersymmetry In Pdm Quantum Systemsmentioning
confidence: 99%